2019
DOI: 10.1021/acs.joc.9b00866
|View full text |Cite
|
Sign up to set email alerts
|

Cu-Catalyzed Arylation/Acyl Migration Cascade Reaction of Enaminones: Access to N-Fused Polycyclic and 2,3-Disubstituted Indoles

Abstract: An efficient synthesis of N-fused polycyclic and 2,3-disubstituted indoles by copper-catalyzed direct annulation/acyl migration reaction of enaminones is reported. This strategy features cheap and low loading of the catalyst/ligand, readily available starting materials, and good functional group compatibilities. Notably, allyl-containing substrates are also tolerated, which allows the downstream derivatization toward indole alkaloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…The N7 / N9 -transferrocenoylation in purines may be classified as an intramolecular acyl migration, which is of special importance in organic and medicinal chemistry. An acyl shift occurs frequently in carbohydrates, lipids, or peptides and serves as a reaction channel in prodrug design and various synthetic strategies. So far, however, only a few studies have coupled experimental and computational methods to clarify the underlying mechanism. In this work, a cluster of earlier relevant examples, including imidazole rings and benzotriazoles, , has been expanded to purines.…”
Section: Introductionmentioning
confidence: 99%
“…The N7 / N9 -transferrocenoylation in purines may be classified as an intramolecular acyl migration, which is of special importance in organic and medicinal chemistry. An acyl shift occurs frequently in carbohydrates, lipids, or peptides and serves as a reaction channel in prodrug design and various synthetic strategies. So far, however, only a few studies have coupled experimental and computational methods to clarify the underlying mechanism. In this work, a cluster of earlier relevant examples, including imidazole rings and benzotriazoles, , has been expanded to purines.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the Cu-catalyzed/promoted arylation reactions, Pd-catalyzed intramolecular enaminone coupling was also documented and suggested to operate through two types of mechanisms according to the manner of the cyclization, namely, Heck reaction and α-arylation. [32,33] A detailed mechanistic investigation of such type of reactions was carried out by Nolan group both Scheme 16 CuI-promoted cyclization of N-2-haloaryl-substituted enaminones and synthesis of (+)-aspidospermidine…”
Section: α-Arylative Cyclization Of N-2-haloaryl Enaminonesmentioning
confidence: 99%
“…Five-membered enaminones are widely used as attractive building blocks for the synthesis of structurally diverse heterocycles. 11–24 For example, Liu et al reported the synthesis of N -fused polycyclic and 2,3-disubstituted indoles by the copper-catalyzed direct annulation/acyl migration reaction of cyclic enaminones. 11 In turn, Troin and coworkers showed an efficient route to indole alkaloid synthons via the photochemical cyclization of aryl enaminones.…”
mentioning
confidence: 99%